Influence of the specific load on stability and vibrations of the multimember column with internal cracks - Sokół, Krzysztof; Kuliński, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Slender systems are mostly studied when Euler’s load or follower load is considered. The use of those types of external loads results in well-known divergence or flutter shape of the characteristic curve. In this study, one takes into account the specific load which allows one to obtain an interesting divergence – pseudo flutter shape of characteristic curves on the external load–vibration frequency plane. The curves can change inclination angle as well as one can observe the change in vibration modes along them. The shape of those curves depends not only on the parameters of the slender system but also on loading heads that induce the specific load. In this study, one considers the slender multimember system in which cracks are present and weaken the host structure. The results of theoretical as well as numerical simulations are focused on the influence of the parameters of the loading heads on vibrations, stability, and loading capacity of the investigated system as well as on the possibility of partial reduction of unwanted crack effect.